Artisanal coalho cheese in Sergipe, Brazil: Technological challenges, food safety strategies, and pathways for market valorization (Research, Society and Development, 2026)
Artisanal coalho cheese is among the most prominent dairy products of Northeastern Brazil and holds considerable economic and sociocultural significance in the state of Sergipe. However, artisanal production frequently exhibits technological and microbiological variability, representing persistent challenges to standardization and food safety. The present review addresses this limitation by systematically examining the production techniques, regulatory challenges, and technological innovations associated with artisanal coalho cheese in Sergipe, aiming to propose an integrated strategy that improves product quality and food safety while preserving its cultural and regional identity. The study employed a systematic bibliographic survey guided by predefined inclusion and exclusion criteria. Results indicate that raw milk quality, hygienic-sanitary conditions, and standardization of technological stages directly influence the microbiological and physicochemical quality of the final product. Innovatively, the study proposes an integrated technological strategy combining Good Manufacturing Practices and systematic microbiological monitoring as essential tools to reduce contamination risks and improve product consistency — offering a structured, replicable framework applicable to similar artisanal dairy systems across Brazil. The implementation of current legislation and certifications is identified as essential to regularizing and enhancing the national market recognition of coalho cheese. Future research should address longitudinal assessments of the impacts of Good Manufacturing Practices on microbiological indicators, the use of geographical indication as a valorization tool, and consumer perceptions of sensory quality and cultural identity. The proposed methodology may help advance quality and food safety standards while preserving the authenticity of artisanal coalho cheese in Sergipe.